ВЛИЯНИЕ ЭКЗАМЕНАЦИОННОГО СТРЕССА НА НЕКОТОРЫЕ ПОКАЗАТЕЛИ ЭКГ СТУДЕНТОВ В РАЗНЫЕ СЕЗОНЫ ГОДА (Experimental biology, 2015)
In article influence of seasons of year on daily dynamics of hourly average quantity finished QRS complexes and dynamics of segment ST during 24-sentries of records of an electrocardiogram of students during examination stress is analyzed. Under the influence of stress fall of level and increase of inclination ST is observed, in summer months these changes are more expressed and cover longer time interval. Significantly excess of quantity QRS of complexes is observed during the period before the examination beginning, in summer months such increase of their quantity is shifted for earlier time of days.
Keywords: QRS complex; segment ST